A systematic review of Chinese Language learning strategies in the past decade (2011-2020) - Mizhe, Xi; Ng, Chwee Fang; Abdul Jabar, Mohd Azidan; Jalaluddin, Ilyana (Universiti Putra Malaysia Press, 2021)
Empirical studies and literature on Chinese language learning strategies (CLLS) in China and abroad have outlined theoretical introductions and case descriptions for nearly a decade. Reportedly, studies on CLLS indicated the following characteristics: The study respondents were primarily international students in China gearing towards regionalisation, nationalisation, or localisation. Furthermore, the qualitative study method followed an empirical, comprehensive, and descriptive learning strategy, such as observations and interviews. However, although the factors influencing learning strategies were gradually becoming diversified, several study limitations were identified (uneven regional studies, insufficient research samples, single research methods, and lack of theoretical paradigms in training learning strategies). Hence, researchers needed to conduct in-depth studies and deeply perceive CLLS to promote Chinese learning and teaching.